Household food security and perceptions of food price unfairness in the United States - Nguyen, Ly; Byrne, Anne T.; Hoang, Hoa; Nayga, Rodolfo M. (Journal of the Agricultural and Applied Economics Association, 2025)
Modern measurement of food security in the United States asks consumers about their household conditions, often with reference to whether they have “enough money for food.” However, “enough” may be subjective, with some households holding the view that retail food prices are unfair and therefore unaffordable. This study determines the association between food insecurity and perceptions of retail food price fairness using online data. Applying ordered probit models, our results show a statistically significant difference in perceptions of fairness cross levels of household food security status. Therefore, understanding perceptions of food price fairness may be an important component of understanding food insecurity in the United States.